2022
DOI: 10.1111/1744-9987.13926
|View full text |Cite
|
Sign up to set email alerts
|

Associations between liver function parameters and poor clinical outcomes in peritoneal dialysis patients

Abstract: Patients with end-stage renal disease (ESRD) have significantly lower survival rates compared with the general population of the same age. Peritoneal dialysis (PD) is an effective treatment for patients with ESRD, but the clinical outcome of PD patients is still not promising. The survival of PD patients is associated with various clinical factors, and exploring some valid risk predictors may be beneficial for this population. In this review, by integrating the latest research, we summarized the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…GGT resulted in being independent foretelling indicator of cardiovascular disease. In addition to that, GGT also occurred as an independent and strong indicator for cardiovascular related mortality in patients undergoing dialysis 10 . On the other hand, only a few studies are found related to the association of GGT with the risk of cardiovascular disease in predialysis chronic kidney disease patients.…”
Section: Resultsmentioning
confidence: 90%
“…GGT resulted in being independent foretelling indicator of cardiovascular disease. In addition to that, GGT also occurred as an independent and strong indicator for cardiovascular related mortality in patients undergoing dialysis 10 . On the other hand, only a few studies are found related to the association of GGT with the risk of cardiovascular disease in predialysis chronic kidney disease patients.…”
Section: Resultsmentioning
confidence: 90%
“…36 PAB, a substance synthesized by the liver, and its associated markers provide insight into the nutritional status of the patient and highlight abnormalities in liver cell synthesis and metabolic functions. 63,64 The significant correlation between AST, T-BIL, D-BIL, G, A/G, PAB, and CDRV undersores the complex relationship between VPA and liver damage.…”
Section: Discussionmentioning
confidence: 99%